Application of Lean Manufacturing to increase operational excellence: A case study in a company in the mining (Research, Society and Development, 2023)
This article comprises a study on the application of the Lean Manufacturing (LM) methodology together with the Kaizen tool for developing continuous improvement projects in a mining company. The main objective of the study was to increase the physical availability of equipment in a large mine, referring to the infrastructure fleet, more precisely tracked tractors. As a characterization of the research, it can be classified as a case study of an applied nature, with a descriptive objective. By applying this methodology, we see greater employee engagement in their improvement actions within the company, where they directly understand their role in each stage of the production process, thus adding value to the product. Through the development of this project, it was possible to motivate employees to improve their work environment and discover different ways of carrying out their activities, thus bringing greater recognition from other employees and leadership, developing professionals brought and trained to the work environment.